Perceived Meanings by Women and Men Employees Analysis of Thailand Life Insurance Commercial “Silence of Love” - Aditya Putri Goentoro (Institute of Research and Community Outreach - Petra Christian University, 2021)
Advertisement is one of the ways that are still popularly used by various companies in creating brand awareness of the products they want to sell. In this study, the writer wanted to find out the differences and similarities in men and women’s perceived meanings of the verbal and visual expressions in the Thailand Life Insurance advertisement titled “Silence of Love”. The writer using the semiotic analysis tools of connotation and denotation. From the study, the writer found that both respondents focused on the plot because of the broad image and the message the company conveyed. However, both respondents had heightened emotional intensity which made them remember that the ad is from a specific Thailand insurance company.Key Words: Advertisement, Semiotics, Life Insurance, Verbal and Visual Expressions